Endothelial Dysfunction in South African Youth Living With Perinatally Acquired Human Immunodeficiency Virus on Antiretroviral Therapy. (13th April 2020) - Mahtab, Sana; Zar, Heather J; Ntusi, Ntobeko A B; Joubert, Susan; Asafu-Agyei, Nana Akua A; Luff, Norme J; Jele, Nomawethu; Zuhlke, Liesl; Myer, Landon; Jao, Jennifer
Abstract: Background: Human immunodeficiency virus (HIV) and antiretroviral therapy (ART) confer cardiovascular disease (CVD) risk in adults with HIV. Few studies have assessed endothelial dysfunction (ED), an early marker of subclinical CVD risk, in youth living with perinatally acquired HIV (YLPHIV). Methods: Using peripheral arterial tonometry, we compared ED in YLPHIV and age-matched youth without HIV. A reactive hyperemic index ≤1.35 was defined as ED. Eligible participants included those aged 9–14 years and on ART ≥6 months at enrollment. Results: Overall, 431 YLPHIV and 93 youth without HIV with a median age of 14.1 versus 13.9 years, respectively, were included. YLPHIV had a lower BMI z score (BMIZ; −0.2 vs 0.4; P < .01) but higher rates of hypercholesterolemia (10% vs 1%; P = .01) than youth without HIV. Among YLPHIV, mean log viral load (VL) was 4.83 copies/mL with 21.7% having a CD4 count <500 cell/mm 3 ; median duration on ART was 9.8 years with 38% initiating at <2 years of age. YLPHIV had higher rates of ED than youth without HIV (50% vs 34%; P = .01); this relationship persisted after adjusting for age, sex, BMIZ, elevated BP, and hypercholesterolemia (RR, 1.43; P = .02). Among YLPHIV, CD4 count >500 cell/mm 3 (RR, 1.04; P = .76), VL (RR, 1.01; P = .78), and current ART class (protease inhibitor based vs nonnucleoside inhibitor based: relative risk, 0.90; P = .186) were not associated with ED after adjustment. Conclusions: Even after adjusting for physiologic differences, YLPHIV appear to be at increased risk of ED compared with age-matched youth without HIV. These findings have important implications for the life course of YLPHIV who may be at increased risk of premature CVD and complications. Abstract : Youth living with perinatally acquired human immunodeficiency virus (HIV) appear to be at increased risk of endothelial dysfunction compared with age- and sex-matched youth without HIV in South Africa, suggesting that HIV plays a role in the progression of vascular disease and future atherosclerosis in youth living with perinatally acquired human immunodeficiency virus.